Benefit-Based Corruption Eradication Policy: A Comparison Between Indonesia and the UK - Lasmadi, Sahuri; Sukma, Ahmad Novindri Aji (Journal of Law and Legal Reform, 2025)
This research analyzes benefit-based corruption eradication policies in Indonesia and the UK while exploring the fundamental differences in anti-corruption strategies in the two countries and the possibility of implementing more effective policies in Indonesia. The method used in this research is normative juridical with a literature study approach. The results indicate that Indonesia and the UK adhere to different approaches to combating corruption. The UK implements a system based on legal certainty, transparency, and strict accountability while instilling a culture of integrity in the government system and the private sector. In addition, the UK has an independent anti-corruption agency with strict regulations integrated into the national legal system. However, policies in Indonesia still face challenges in terms of law enforcement, independence of anti-corruption institutions, and transparency of state financial management. To improve the effectiveness of corruption eradication in Indonesia, this research recommends a policy reconstruction that draws on UK practice. This measure includes strengthening independent anti-corruption institutions, implementing a stricter transparency system, and integrating anti-corruption policies into all national regulations. Applying the principle of expediency in corruption eradication policies is expected to foster a more effective, accountable, and sustainable system in corruption eradication in Indonesia.